2017
DOI: 10.1002/cncr.31057
|View full text |Cite|
|
Sign up to set email alerts
|

Transcriptional alterations in hereditary and sporadic nonfunctioning pancreatic neuroendocrine tumors according to genotype

Abstract: Distinct mRNA expression patterns were identified in sporadic-associated, VHL-associated, and MEN1-associated NFPanNETs. The current results uncover new pathways involved in NFPanNETs that are subtype-specific and provide potential new diagnostic or therapeutic targets based on tumor subtype. Cancer 2018;124:636-47. © 2017 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 45 publications
1
11
0
1
Order By: Relevance
“…-upregulation of genes related to hypoxia-inducible factor molecules, angiogenesis, epithelial mesenchymal transition and/or metastasis, cell cycle and growth factors and receptors (114), -and hypomethylated CpGs, significantly more common in VHL-related versus sporadic and MEN1-related NETs (115).…”
Section: Vhlmentioning
confidence: 99%
See 1 more Smart Citation
“…-upregulation of genes related to hypoxia-inducible factor molecules, angiogenesis, epithelial mesenchymal transition and/or metastasis, cell cycle and growth factors and receptors (114), -and hypomethylated CpGs, significantly more common in VHL-related versus sporadic and MEN1-related NETs (115).…”
Section: Vhlmentioning
confidence: 99%
“…- and hypomethylated CpGs, significantly more common in VHL-related versus sporadic and MEN1-related NETs ( 115 ).…”
Section: Digestive Neuroendocrine Neoplasms In Phakomatosesmentioning
confidence: 99%
“…Gene expression analysis was performed as described previously. 28 Briefly, sample labeling and array hybridization were performed according to the Agilent 1-color microarray-based gene expression analysis protocol (Agilent Technologies). Total RNA from each sample was linearly amplified and labeled.…”
Section: Gene Expression Analysismentioning
confidence: 99%
“…As MEN1 is also one of the most important driver genes in sporadic pNETs (Jiao et al 2011, Scarpa et al 2017, evidence gained from sporadic pNETs might be applied to MEN1-related pNETs as well. Indeed, cumulative methylation index was found not to be statistically different between MEN1-related and sporadic NF-PNETs (Conemans et al 2018a), the prognostic value of ARX/PDX1 IHC was found to be similar in MEN1related and sporadic nf-PNETs (Cejas et al 2019) and mRNA expression analysis has revealed that a subgroup of sporadic pNETs clustered with MEN1-related pNETs, while others clustered alone (Keutgen et al 2018). All this lends credence to the fact that at least a subgroup of sporadic (NF)-pNETs -those with somatic MEN1 mutations?is biologically comparable to MEN1.…”
Section: Discussionmentioning
confidence: 96%